Photovoltaic storage system enhancement-based supercapacitor control - Soliman, Ahmed Mahmoud; Elbaset, Adel A.; Eldeen, Ashraf Nasr (Institute of Advanced Engineering and Science, 2026)
This paper discusses the improvement of the storage system by getting a stable voltage, with a large inrush current for the battery. The battery system (BESS) is the most important component of a photovoltaic (PV) system. Its large size allows it to provide the desired high peak discharge currents and extend its lifespan. Our work focuses on control the integration of super capacitors (SC) with batteries in order to maximize the battery's power supply, reduce the ripples caused by light changes photovoltaic cells, improve the battery lifespan and supply the useful high peak power for a short periods of time for the big loads (like motors, trains, and big mechanisms,), Super capacitors (SCs) can do that since their internal architecture does not include chemical solutions, which will result in high power densities and higher charge and discharge currents, also lower energy densities. These lower energy densities will be compensated by a combination and integration with the battery, especially the lead-acid battery. Focusing on the lead acid due to drawbacks like short lifetime, low number of cycles. from that combination by switching the control circuit, it can increase the battery lifetime and remove the stress, especially in high current loads, reducing abnormal battery temperature, and ensuring a significant mass reduction of the energy storage system as all. Also, by supporting the SC with a buck boost converter control, keeping the voltage stable, preventing the PV voltage changing problems from the PV cell to any storage systems.